Council tax valuation band predicts breast feeding and socio-economic status in the ALSPAC study population - Herrick David; Taylor Gordon; Peart Carole; Gwynne Mark; Kane Gill; Beale Norman; Boyd Andy (BMC, 2006)
Abstract Background Breast-feeding rates in the UK are known to vary by maternal socio-economic status but the latter function is imperfectly defined. We test if CTVB (Council Tax Valuation Band - a categorical assessment of UK property values and amenities governing local tax levies) of maternal address predicts, in a large UK regional sample of births, (a) breast-feeding (b) personal and socio-economic attributes of the mothers. Methods Retrospective study of a subset (n.1390 selected at random) of the ALSPAC sample (Avon Longitudinal Study of Parents and Children), a large, geographically defined cohort of mothers followed from early pregnancy to 8 weeks post-delivery. Outcome measures are attitudes to breast-feeding prior to delivery, breast-feeding intention and uptake, demographic and socio-economic attributes of the mothers, CTVB of maternal home address at the time of each birth. Logistic regression analysis, categorical tests. Results Study sample: 1360 women divided across the CTVBs - at least 155 in any band or band aggregation. CTVB predicted only one belief or attitude - that bottle-feeding was more convenient for the mother. However only 31% of 'CTVB A infants' are fully breast fed at 4 weeks of life whereas for 'CTVB E+ infants' the rate is 57%. CTVB is also strongly associated with maternal social class, home conditions, parental educational attainment, family income and smoking habit. Conclusion CTVB predicts breast-feeding rates and links them with social circumstances. CTVB could be used as the basis for accurate resource allocation for community paediatric services: UK breast-feeding rates are low and merit targeted promotion.